Analysis of the Influence of Organizational Behavior and Accounting System Implementation on Financial Performance: A Case Study of PT. Bank BRI Using a Quantitative Approach - Burhanuddin, Burhanuddin (PT Maju Malaqbi Makkarana, 2024)
This study aims to analyze the influence of organizational behavior and the implementation of accounting systems on the financial performance of PT Bank Rakyat Indonesia (Persero) Tbk (Bank BRI). A descriptive verification method with a quantitative approach was employed to achieve this objective. The study used secondary data derived from the published annual financial report of PT Bank BRI for the 2022 period, obtained from the official Indonesia Stock Exchange website. The total sampling technique was applied, resulting in a single sample encompassing the entire population. Data analysis techniques used in this study include descriptive test analysis, T-test, and crosstab analysis. The findings reveal a significant and positive relationship between organizational behavior and financial performance at Bank BRI. These results align with prior research, indicating that strong organizational culture and commitment positively influence financial reporting accuracy and compliance with organizational regulations. The study underscores the importance of modern, integrated accounting systems and ethical organizational behavior in enhancing financial management and achieving sustainable performance.